Building the Foundation for Culturally Responsive Pedagogy in Classrooms - Jacobs, Virginia G (East Carolina University, 2023)
This study examined how teachers and leaders could work together to build capacity for culturally responsive pedagogy that influenced the school culture. Using Participatory Action Research (PAR) as the primary methodology, educators work together to understand Culturally Responsive Pedagogy (CRP) and integrate pedagogical principles into their curriculum and practices. The research revealed educators' surface relationships with students in the areas of access and inclusion. Educators had surface relationships with students and families due to challenges and barriers of fear and avoidance due to their experiences within the school community. During the three PAR cycles, teachers resolved that if they wanted to reach all students, they must know how to make learning relevant and relatable. To accomplish this, teachers must build and foster relationships, by learning and understanding their students, families, backgrounds, and experiences. Doing so will allow them to create and implement culturally responsive practices intentionally. As a result of the study, we are making incremental growth in culturally responsive pedagogy. Despite teachers' willingness and effort to effectively serve students and families, teachers had a surface level of cultural understanding. Ultimately, we desired for our teachers and staff to embark on a transformation to integrate and immerse the environment, curriculum, and practices in culturally responsive pedagogy, one classroom at a time. This study's results can guide leaders who expect quick radical change to recognize small increments of progress while creating a strategic plan for total school improvement. Further research study needs to examine professional identity development and wellness support for Principals of Color working in predominantly white spaces.
Keywords: culturally responsive pedagogy; culturally responsive teaching; Culturally relevant pedagogy; Educational leadership; School environment; Teacher-student relationships